A construção da relação “Brasil - Estados Unidos” na revista Veja - Belmonte, Wagner Barge (2016)
This research investigates how Veja’s enunciator covers the political and economic relations between Brazil and the United States, as well as their foreign relations. Editora Abril’s magazine frequently presents the American society as a role model. Within its discourse’s nodal points, the communication contract, based on the Civita family’s business and market goals, associates Capitalism to the idea of prosperity and freedom. Even when covering conflicts and wars, the United States appear before their enemies as a powerful holder of cutting edge technologies – while those enemies have no arsenal to fight back, but still represent a threat to the West. The corpus is made of magazine covers and articles that have the bilateral relation enunciated by Veja since its first year (1968) as their subject. The research’s goal is to understand how the magazine builds, through its nodal points, the idea that the United States are a role model to inspire Brazil as a nation, be it from the political and economic point of view, or for the relationship their citizens have with the State and the established political powers. The values incorporated in the coverage are presented. Our thesis is that, besides suggesting a neocolonial model for Brazil, focused on the American society’s political and economic values, the enunciator relies on the economic liberalism’s ideological spectrum to adopt conservative and traditional positions, especially with political matters. As for the research methodology, it is based on the discourse analysis proposed by Laclau, Mouffe, Prado, Charaudeau and Žižek. For a reflection on the press as a whole, we based our studies on Fausto, Sousa Santos, Chomsky and Arbex Jr. We expect this work to contribute to and deepen the debate about how the relations between Brazil and the United States are presented, historically speaking, on the verge of the magazine’s 50th year anniversary